Phytotoxicity of zinc oxide nanoparticles and multi-walled carbon nanotubes, alone or in combination, on Arabidopsis thaliana and their mutual effects on oxidative homeostasis. - Shaohui Yang; Rong Yin; Chen Wang; Yongkui Yang; Jiehua Wang (PLoS ONE, 2023)
The extensive use of engineered nanoparticles (ENPs) has raised concerns about their potentially harmful effects on the ecosystem. Despite previous reports of a variety of individual ENPs, the mutual effects of ENPs when used in combination were not well understood. In this study, we first investigated the effects of different sizes and concentrations of ZnO nanoparticles (ZnO NPs) or multi-walled carbon nanotubes (MWCNTs) on the growth performance of Arabidopsis thaliana seedlings. Then, two concentrations of ZnO NP (40 and 50 mg/L) with a diameter of 90 nm and MWCNTs (100 and 500 mg/L) with an outer diameter of 40-60 nm were used to evaluate their respective or simultaneous phytotoxicity to Arabidopsis. The results showed that seedlings exposed to either ZnO NPs or MWCNTs exhibited significant phytotoxic symptoms. ZnO NPs caused stronger inhibitory effects than MWCNTs on several plant growth indices, including reduced root length, chlorophyll content, and increased ROS concentration. When applied together, the concurrent effects of ZnO NPs and MWCNTs on Arabidopsis seedlings appeared to be more negative, as evidenced not only by the further deterioration of several growth indices but also by their synergistic or additive regulation of the activities of several antioxidant enzymes such as superoxide dismutase (SOD), catalase (CAT) and glutathione reductase (GR). Moreover, qRT-PCR analysis revealed that in the presence of ZnO NPs and MWCNTs, the expression of genes important for maintaining cellular ROS homeostasis was differentially regulated in shoots and roots of Arabidopsis seedlings. Overall, our data may provide new insights into how plants respond to more than one type of nanomaterial and help us better understand the associated environmental risks.